Effect of Ribs Configurations on Heat Transfer Enhancement for W-Shaped Ribs in a Square Duct - Gajghate, Sameer Sheshrao; Deshpande, Onkar Prakash; Desai, Amit Uttam; Deshmukh, Akshay Dilip; Kharade, Shrikant Uttam; Pal, Sagnik; Cardoso, Elaine Maria [UNESP]; Saha, Bidyut Baran; Bhaumik, Swapan [UNESP] (Springer Nature, 2023)
In this research, three W-shaped ribs are taken to analyze their influence on the heat transfer rate in the internal cooling of a gas turbine blade at constant e/Dh (0.037) and heat flux. The ribs are located on rectangular channels in a square duct, and the experiments are conducted for low Reynolds numbers (12,000–20,000). The influence of Reynolds number, pitch ratios (4.28, 5.71, and 7.14), rib shape, and rib angle (45°, 50°, and 55°) on the area-averaged heat transfer, friction factor, and thermal performance is analyzed. The experimental values of the Nusselt number and friction factor obtained from the smooth channel fit well with Dittus–Boelter and Blasius correlations. The Nusselt number increases with an increase in pitch ratio. The friction factor decreases by 3.5, 5.3, and 7.1 times for the W rib turbulator as the rib angle increases compared with the smooth channel. The present work reveals higher thermal performance than other studies based on ribs dimension, shape, pressure drop, frictional losses, and Reynolds number (12,000–20,000). Accordingly, using these geometric parameters, a new correlation of Nusselt number and friction factor is developed and compared with the experimental results. The Nusselt number and friction factor deviation were ± 6% and ± 11%, respectively.
Keywords: Area-averaged heat transfer enhancement; Friction factor; Pitch ratio; Reynolds number; Rib angle; W-shaped rib turbulator